CD4+ T cells participate in the nephropathy of canine visceral leishmaniasis - F.A.L. Costa; J.L. Guerra; S.M.M.S. Silva; R.P. Klein; I.L. Mendonça; H. Goto (Brazilian Journal of Medical and Biological Research, 2000)
Renal involvement in visceral leishmaniasis (VL) is very frequent. The renal lesions of humans and dogs are similar but their pathogenesis has not been clearly elucidated. There is growing evidence that the cellular immune response is involved in the pathogenesis of immunologically mediated glomerulonephritis. Since T cells could participate in the pathogenesis of nephropathy, in the present study we investigated the possible involvement of CD4+ and CD8+ T cells in the nephropathy of canine VL. Six dogs naturally infected with Leishmania (Leishmania) chagasi from the endemic area in the Northeast of Brazil, the town of Teresina in the State of Piauí, were studied. An expressive inflammatory infiltrate of CD4+ T cells both in glomeruli and in interstitium was present in 4 animals and absent in 2. CD8+ T cells were detected only in one animal. CD4+ T cells alone were observed in 3 animals; when CD8+ T cells were present CD4+ T cells were also present. CD4+ T cells were observed in cases of focal segmental glomerulosclerosis, diffuse membranoproliferative glomerulonephritis, diffuse mesangial proliferative glomerulonephritis and crescentic glomerulonephritis. CD8+ T cells were present only in a case of crescentic glomerulonephritis. Leishmania antigen was detected in glomeruli and in interstitial inflammatory infiltrate in 4 animals and immunoglobulins were observed in 4 dogs. In this study we observed that T cells, in addition to immunoglobulins, are present in the renal lesion of canine VL. Further studies are in progress addressing the immunopathogenic mechanisms involving the participation of immunoglobulins and T cells in canine VL nephropathy.